Investigating the local circulation of the southeast Cape Basin - Carr, Matthew David (Department of Oceanography, 2018)
Located off the west coast of southern Africa, the southeast Cape Basin is characterised by a unique combination of strong coastal upwelling and vigorous offshore mesoscale variability. The juxtaposition of offshore mesoscale variability and coastal upwelling results in a complex and dynamic environment. In this study a combination of in situ Acoustic Doppler Current Profiler (ADCP) data and satellite observations were used to identify, describe and characterise the features driving the local circulation within the southeast Cape Basin. The ADCP data was obtained from the South Atlantic MOC Basin-wide Array (SAMBA), which included four deep sea moorings located along ~34.5°S on the 1000, 2000, 3000 and 4500m isobaths respectively. There was a distinct difference in the circulation observed at the mooring located on the shelf edge (1000m) and the moorings further offshore (2000m, 3000m and 45000m). The offshore circulation, observed by the moorings located on the 2000, 3000, 4500m isobaths, were driven by large mesoscale eddies, both cyclonic and anticyclonic, originating at the Agulhas retroflection and within the Cape Basin itself. The mesoscale eddies induced high speed baroclinic transport events which impacted the upper water column to a depth of at least 400m. The in situ observations were used to show the precise characteristics of two cyclonic shelf eddies and one anticyclonic eddy through the upper water column (~50 to 500m). The analysis of these features was important as the physical characteristics of both the cyclonic shelf eddies and anticyclonic eddies through depth are not well known. Considering the short period of observations (18th September 2014 to 1st December 2015), the analysis was not used to assume the prevailing physical characteristics of cyclonic shelf eddies and anticyclonic eddies. Instead the analysis showed the potential for future long term studies to use the sustained in situ observations from the SAMBA mooring array and similar analysis to define the precise characteristics of mesoscale eddies through depth. This will greatly improve the understanding of how these features influence the interocean exchange between the Indian and Atlantic Oceans. The circulation at the shelf edge, observed by the mooring located on the 1000m isobath, was shown to be driven by a combination of offshore mesoscale eddies, the position of the upwelling front and warm filaments formed at the reflection of the Agulhas Current. Identifying the influence of both the offshore mesoscale eddies and coastal upwelling at the shelf edge showed connectivity between the upwelling system and the offshore mesoscale variability. An example of the connectivity between the offshore mesoscale variability and the upwelling front was identified and presented. A dipole formed by two mesoscale eddies was observed to induced cross shelf transport advecting productive shelf waters offshore. The in situ observations were used to calculate the amount water transported from the shelf to the open ocean during this cross shelf transport event. The filament representing the cross shelf transport event was calculated to have a total volume of ~2 x 10¹² m³ with a volume transport of ~1Sv suggesting the event would have had a substantial impact on the local biology. The detailed analysis and quantification of the cross shelf transport event aimed to improve the current understanding of how mesoscale features interact with the upwelling system. In situ observations of cross shelf transport are rare, therefore the quantification of the amount of transported in the cross shelf transport event can serve as a baseline for future studies attempting to assess the impact of comparable cross shelf transport events on the local biology.